2019
DOI: 10.2478/aiht-2019-70-3159
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and selenocompounds inhibit 3,5-dimethylaminophenol toxicity to human urothelial cells

Abstract: Exposure to alkyl anilines may lead to bladder cancer, which is the second most frequent cancer of the urogenital tract. 3,5-dimethylaniline is highly used in industry. Studies on its primary metabolite 3,5-dimethylaminophenol (3,5-DMAP) showed that this compound causes oxidative stress, changes antioxidant enzyme activities, and leads to death of different mammalian cells. However, there is no in vitro study to show the direct effects of 3,5-DMAP on human bladder and urothelial cells. Selenocompounds are sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…SeMet acted as an antioxidant to prevent cholestasis‐induced liver damage and inflammation (Brzački et al., 2019), and it also alleviated T‐2 toxin (type A trichothecenes)‐induced oxidative stress, inflammatory response, intestinal barrier damage, and kidney injury (Liu, Dong, et al., 2020; Liu, Yang, et al., 2020). SeMet and selenite both reduced 3,5‐dimethylaminophenol‐induced oxidative stress, DNA damage, and apoptosis in human urothelial cells, and SeMet at a concentration of 10 μmol/L exerted protecting effect equal to that of selenite at a concentration of 30 μmol/L (Erkekoglu et al., 2019). SeMet supplementation resulted in a higher feed intake and higher levels of total Se, SELENOP, SeAlb, and SeMet in sow colostrum than selenite supplementation (Falk et al., 2019).…”
Section: Selenium Species In Cereals and Human Healthmentioning
confidence: 99%
“…SeMet acted as an antioxidant to prevent cholestasis‐induced liver damage and inflammation (Brzački et al., 2019), and it also alleviated T‐2 toxin (type A trichothecenes)‐induced oxidative stress, inflammatory response, intestinal barrier damage, and kidney injury (Liu, Dong, et al., 2020; Liu, Yang, et al., 2020). SeMet and selenite both reduced 3,5‐dimethylaminophenol‐induced oxidative stress, DNA damage, and apoptosis in human urothelial cells, and SeMet at a concentration of 10 μmol/L exerted protecting effect equal to that of selenite at a concentration of 30 μmol/L (Erkekoglu et al., 2019). SeMet supplementation resulted in a higher feed intake and higher levels of total Se, SELENOP, SeAlb, and SeMet in sow colostrum than selenite supplementation (Falk et al., 2019).…”
Section: Selenium Species In Cereals and Human Healthmentioning
confidence: 99%
“…Accordingly, oxidation of alkyl anilines is generally regarded as a critical bioactivation. Indeed, studies have shown that the major metabolite of 3,5-DMA and 3,5-dimethylaminophenol (3,5-DMAP) is responsible for the ROS production, which contributes to the apoptotic cytotoxicity in mammalian cell lines [113,114]. Furthermore, a recent in vivo study has shown that 3,5-DMA-induced ROS production disrupts the dendrites patterning of the cortical cells and causes the abnormal cortical layer distribution in developing fetal brain [115].…”
Section: The Impact Of Atypical Neurotoxins On the Developing Brainmentioning
confidence: 99%
“…SeMet provides Se for the synthesis of selenoproteins such as Gpx1. Se-Met can enhance antioxidant capacity and reduce oxidative stress 13,14 .…”
Section: Introductionmentioning
confidence: 99%